The use of cloud and fog technologies in the educational process of a higher education institution - Prokopenko А. (Problems of Engineer-Pedagogical Education, 2021)
The research is devoted to the questions of applying cloud and fog technologies in the educational process of higher education institutions. The article considers the issues of improvement and modernization of the management and educational component of higher education institutions through the use of cloud and fog technologies. The author of the article on the basis of the analysis of scientific, pedagogical, administrative and specialized literature proves the relevance and prospects of research in this direction. The study presents the most popular services which can be used in the educational process, namely: Google Alerts, Google Analytics, Google Art Project, Google App Engine, Google Apps, Google Merchant Center, Blogger, Google Calendar, Google Classroom, Google Docs, Google Drive, Google Mobile, Google Sites, YouTube and more. One of the key aspects of solving this issue is the author's conclusion that cloud computing is by no means a replacement for cloud technologies, but on the contrary it is a continuation of this idea of storing and processing information flows, since, from the perspective of cloud computing, cloud technologies repeatedly increase their positive impact on the digitalization of the educational process. The expediency of developing and implementing an educational and scientific laboratory, which will deal with the use of innovative (cloud and fog) technologies in the educational process of higher education, is substantiated. The article defines the purpose, tasks and functions of the educational and scientific laboratory. The author concludes that the use of cloud and fog technologies will improve the management in higher education, enhance the educational process for training future professionals in educational specialties for the system of higher education, and improve the skills of scientific and pedagogical staff of the education institution. The author considers the introduction of innovative technologies for testing the effectiveness of cloud and fog technologies in the activities of higher education institutions to be a prospective niche for further scientific research.